The Mediating Role of Liquidity in the Relationship between ESG Performance and Firm Size: Evidence from IDX ESG Leaders - Wenny Djuarni; Muhammad Zaky (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2026)
Purpose – his study examines the effect of Environmental, Social, and Governance (ESG) performance on firm size, with liquidity as a mediating variable, among issuers listed in the IDX ESG Leaders index. The research responds to the growing emphasis on sustainability in Indonesia’s sharia-compliant growth stock market. Method – A quantitative approach is employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The analysis is based on secondary cross-sectional data from 30 issuers over the 2025 period.. Implications – The results indicate that ESG performance has no significant direct effect on either firm size (p = 0.613) or liquidity (p = 0.735). However, liquidity exhibits a significant negative effect on firm size (p = 0.017). The indirect effect of ESG on firm size through liquidity is also not significant (p = 0.771). These findings suggest that ESG adoption in emerging markets like Indonesia may still be symbolic, challenging the assumption of short-term financial benefits. The study highlights the need for contextualized models and stronger regulatory frameworks by OJK (Indonesia’s Financial Services Authority). The results imply that the anticipated financial outcomes of ESG practices may not materialize in the short term within emerging markets, underscoring the importance of long-term perspectives and enhanced regulatory support.